PENGARUH TEKNIK RELAKSASI DAN TEKNIK DISTRAKSI TERHADAP PERUBAHAN INTENSITAS NYERI PADA PASIEN POST OPERASI DI RUANG IRINA A ATAS RSUP PROF. DR. R. D. KANDOU MANADO - Rampengan, Stania F.Y; Rondonuwu, Rolly; Onibala, Franly (Universitas Sam Ratulangi, 2014)
ABSTRACT : Pain is a sensation of discomfort that is individualized. Pain is the main reason for a person to seek medical assistance. Pain occurs with many disease processes or concurrent with some diagnostic examination or treatment. Pain is very annoying and troublesome more people than any disease (Brunner & Suddarth, 2002). The purpose of this study was to determine the effect of relaxation techniques and distraction techniques to the pain intensity changesin post-surgery patients. This research was conducted by the Quasi Experiment with